2005
DOI: 10.1523/jneurosci.0523-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinesia Induced by Dopamine D2 Receptor Blockade Is Associated with Reduced Motor Cortex Activity in the Rat

Abstract: Disruption of motor cortex activity is hypothesized to play a major role in the slowed movement (bradykinesia) associated with reduced dopaminergic function. We recorded single neurons in the motor cortex of free-moving rats performing a forelimb-reaching task. The same neurons were examined before and after induction of bradykinesia with the D 2 dopamine receptor antagonist haloperidol. Withincell changes in the firing rate and firing pattern of individual cells and the correlation between simultaneously reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 80 publications
6
70
2
1
Order By: Relevance
“…For example, in studies with Parkinson's patients, placebo effects have been shown to be partially mediated by dopamine release in the striatum contributing to changes in motor function and performance (e.g., Goetz, Leurgans, Ramman, & Stebbins, 2000) with the degree of dopamine release related to the expectation of clinical benefit (de la Fuente-Fernandez et al, 2001). Changes in dopaminergic function also mediate motor cortex activity, which may alter motor unit recruitment in the spinal cord (e.g., Parr-Brownlie & Hyland, 2005), while recent PET studies demonstrate that placebos activate the limbic system (de la Fuente-Fernandez et al, 2002). One possible explanation, therefore, is that expectancy-induced changes in neural drive produced improved motor unit recruitment and force production.…”
Section: Downloaded By [Laurentian University] At 04:45 08 December 2014mentioning
confidence: 99%
“…For example, in studies with Parkinson's patients, placebo effects have been shown to be partially mediated by dopamine release in the striatum contributing to changes in motor function and performance (e.g., Goetz, Leurgans, Ramman, & Stebbins, 2000) with the degree of dopamine release related to the expectation of clinical benefit (de la Fuente-Fernandez et al, 2001). Changes in dopaminergic function also mediate motor cortex activity, which may alter motor unit recruitment in the spinal cord (e.g., Parr-Brownlie & Hyland, 2005), while recent PET studies demonstrate that placebos activate the limbic system (de la Fuente-Fernandez et al, 2002). One possible explanation, therefore, is that expectancy-induced changes in neural drive produced improved motor unit recruitment and force production.…”
Section: Downloaded By [Laurentian University] At 04:45 08 December 2014mentioning
confidence: 99%
“…However, these drugs also induce extrapyramidal motor side effects by reducing basal ganglia output (Parr-Brownlie and Hyland, 2005). Although the newer, so-called atypical antipsychotics have a reduced liability to trigger extrapyramidal side effects, they induce intolerable metabolic side effects (Manu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have attempted to investigate the relationship between motor cortex activity and PD progression, although results have been controversial. Cortical activity has been found to be reduced (Escola et al, 2002(Escola et al, , 2003Buhmann et al, 2003;Lefaucheur, 2005;Parr-Brownlie and Hyland, 2005;Brown et al, 2009), increased (Sabatini et al, 2000;Pelled et al, 2002;Seiss andPraamstra, 2004, Lefaucheur, 2005), or unchanged (Dick et al, 1984;Metz et al, 2004) in parkinsonian animals as well as PD patients. This variability can be attributed to experimental reasons (i.e., methods, time, and region of interest).…”
Section: Introductionmentioning
confidence: 99%